Kelayakan Shampo Berbahan Dasar Lidah Buaya Dan Jeruk Nipis Untuk Perawatan Rambut Rontok - Sari, Syakira Kurnia; Lasmi, Nadia; Putri, Fidella Eriza; Ariyani, Fharadita; Miga Dewi, Siska; Saputra, Indra; Wanti, Hilda (Universitas Negeri Jakarta, 2024)
Hair is an important part of head protection from exposure to outside air. The problem of hair loss is suffered by many people. Aloe vera is a natural ingredient that is traditionally used to overcome the problem of hair loss. Some studies show the use of aloe vera can be used as an alternative hair care that plays a role in treating dry hair, strengthening hair roots, and reducing hair loss. Lime is one of the medicinal plants that can be used to kill bacteria that cause dandruff. Objective: Knowing the effectiveness of aloe vera gel extract on hair growth so that hair does not fall out and the scalp is clean anti-dandruff. Method: Experimental research with 9 panelists, including 2 lecturers, 3 general public, and 5 students. Based on the results of this study shows the effect of the use of aloe vera and lime in scalp and hair care on increasing the results of reducing hair loss.Based on experimental results from several samples selected on color with panelists preferring Fr 3, which is attractive with a score of 44.44%. The aroma level with panelists liked on Fr 3 very distinctive smell with a score of 77.77%. The froth power with panelists preferring Fr 3 is quite frothy with a score of 33.33%. The favorability level with the panelists likes FR 3 is very like with a score of 55.55%.